Optimized Conditions for Catalytic Chemical Vapor Deposition of Vertically Aligned Carbon Nanotubes - M. Makenali; R. Ajeian; M. Tavakkoli; M. Nakhaee Badrabadi; S. Panahian Jand; M. Zare (Journal of Sciences, Islamic Republic of Iran)
Here, we have synthesized vertically aligned carbon nanotubes (VA-CNTs), using chemical vapor deposition (CVD) method. Cobalt and ethanol are used as the catalyst and the carbon source, respectively. The effects of ethanol flow rate, thickness of Co catalyst film, and growth time on the properties of the carbon nanotube growth are investigated. The results show that the flow rate of ethanol and the Co layer thickness play important roles on the length and the degree of alignment of the carbon nanotubes. High density VA-CNTs with forest-like structure are grown at a very low ethanol flow rate of 0.8 sccm, which is the optimized flow rate in our experiments. Therefore, the cost of synthesizing VA-CNTs is decreased by a low consumption of ethanol and utilizing the cheap CVD synthesis method. High density of small-sized catalyst particles is formed in the Co-catalyst thickness of 1 and 2nm, resulting in the growth of vertically aligned nanotubes. However, increasing the thickness of Co layer to 10 and 16 nm, leads to the growth of nanotubes parallel to the substrate with the spaghetti-like structure. The experiments reveal that enhancing the growth time from 5 to 120 min can mostly affect the uniformity and length of VA-CNTs.